DESAIN TEMATIK GAME EDUKASI UNTUK PENINGKATAN NILAI KEPEDULIAN DAN KETEKUNAN PADA KARAKTER ANAK DENGAN MODEL ASINKRON - Andy Pramono; Pujiyanto Pujiyanto; AAG Rai Arimbawa (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2019)
According to the Indonesian Ministry of Communication and Informatics data, at least 30 million children and adolescents in Indonesia are internet users, and digital media is currently the main choice of communication channels they use. One of the content that is the choice of users, especially children, is an interactive game. There is a strong assumption that interactive games can inhibit children's education, which makes children lazy to learn. The other side of character education is a target of the Indonesian government. Education about caring and perseverance is an important topic for children's character education. This article will discuss thematic learning media for raising children's awareness and perseverance which combines